Integrated manufacturing of direct 3D-printed clear aligners - Rajasekaran, Abirami; Chaudhari, Prabhat Kumar (Frontiers in Dental Medicine, 2023)
The inception of the laboratory work for a removable tooth moving appliance construction by sectioning the teeth from the malocclusion model to align them with wax and achieve minor dental correction has evolved into a state of digital planning and appliance manufacturing for a wide spectrum of malocclusion. The disruptive technology of directly printing clear aligners has drawn the clinician and researcher's interest in the orthodontic fraternity contemporarily. This workflow enables to the development of an in-house aligner system with complete control over desired aligner thickness, extent, and attachments; also technically resource-efficient with greater accuracy by excluding all the intermediate steps involved in the thermoforming method of manufacturing. This promising exploratory subject demands to be well-received with further research-based improvements. This article intends to summarize the digital orthodontic workflow and the literature evidence.